The Effects of Religion and Poverty on Nigeria’s Development as Portrayed in Yoruba Written Plays - Olufadekemi, Adagbada (NIU Journal of Humanities; Vol 3 No No. 2 (2018): KIU Journal of Humanities, Vol. 3 No. 2, June 2018, 2018)
Nigeria has the resources to be among the affluent and developed nations of the world, wherein her citizens could have the basic needs of life and can individually contribute to the development of the nation without exclusion. This is however not the case; Nigeria is fast becoming one of the poorest countries in the world as 45% of her population live below poverty level - on less than a dollar daily. The literary world is a reflective one, where the image of experiences and occurrences are reflected fictitiously or otherwise. Ethnographically, literature also documents the experiences of a group of people at different times, showing their hopes, aspirations, fears, agitations, socio-economic and religio-political development. The (present) economic condition that is prevalent in Nigeria should be of immense concern to all, the literary artists being no exception. Our focus in this paper therefore, is to examine the extent to which Yorùbá playwrights have portrayed poverty as an endemic issue that is preventing individual and national development, especially in the light of the fact that the Yorùbá are in all things religious. We found out among other things, that misrepresentation and misinterpretations of what qualifies a (Yorùbá) person for Paradise as a Christian, is an important bane of the poor in taking the right steps toward rejecting poverty. This is apart from the non-provision of the basic needs of life by the state, in order to bridge the gap between the rich and the poor. Our suggestion is that empowerment through poverty alleviation programmes by concerned individuals, corporate bodies and the state particularly, will go a long way in coming to the aid of the poor. This is because unless the poor, who could have become poor by his ineptitude or by the prevalent government policies, is catered for, the average and rich persons cannot live their lives peacefully and to the fullest, without disturbance in one form or the other from the poor with their characteristic traits and vices. Keywords: Absolute Poverty, Culture, Religion, Social Exclusion, Empowerment.